Rough and Tough: How Particle Surface Roughness Affects Liquid Marble Formation and Stability - Umair Sultan; Celin Kotulla; Kall Kefle; Syuji Fujii; Nicolas Vogel (Advanced Science)
Abstract Liquid marbles are liquid droplets encased by non‐wetting particles. They exhibit elastic and non‐sticking properties that enable applications such as sensors, adhesives, miniature reactors, and material carriers. The formation, stability, and properties of liquid marbles depend on the physico‐chemical characteristics of the solid particles. This study systematically explores the impact of particle surface roughness on liquid marbles by employing colloidal supraparticles as well‐defined model systems. Supraparticles are spherical aggregates of uniform colloidal primary particles, which enable adjusting the characteristic surface roughness by varying the primary particle size. Increasing surface roughness increases the interfacial contact angle, which, in turn, influences the mechanical properties and liquid marble stability. The presence of surface roughness increases the deformation resistance of the liquid marble, which counteracts the spreading of the inner liquid upon mechanical impact, and therefore hinders rupture. The increased contact angle further enables the formation of liquid marbles from increasingly low‐surface‐tension organic liquids. This study thus provides detailed insights into the structure‐property relationships governing the preparation of stable liquid marbles based on particle surface characteristics.